(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
Vegetation can be defined as a grouping of native plants that occur in any land area, as long as the conditions for their development are met, thus, we can consider it an important element of the ecological environment and essential for the survival of human beings. This work aims to map the vegetation cover of the city of Teófilo Otoni based on remote sensing data. Teófilo Otoni is located in the Northeast of the State of Minas Gerais in Brazil, and has about 141.269 inhabitants. The present study seeks to generate information on the current state of the study area, providing relevant information about the existing vegetation cover in the municipality through the creation of maps using images obtained through the Landsat 8/OLI satellite. For this, the Normalized Difference Vegetation Index (NDVI) was chosen. The results indicate a denser vegetation (more than 0,55 NDVI) in the more distant regions of the urban perimeter and when approaching the urban area, we have a lower vegetation or a sudden change to an area that suffered anthropological action (less than 0,34 NDVI).